Endodontic management of three-canalled mandibular lateral incisor using dental operating microscope. - Vijayakumar Ashwinkumar; Suresh Nandini; Natanasabapathy Velmurugan (Tehran University of Medical Sciences, 2014)
This case report presents endodontic management of a mandibular lateral incisor with three canals using surgical dental operating microscope. This study describes the root canal variation of mandibular lateral incisor and highlights the importance of surgical operating microscope in detecting an unusual canal morphology.